Identification and Characterization of the Succinate Dehydrogenase Complex Iron Sulfur Subunit B Gene in the Oriental River Prawn, Macrobrachium nipponense - Jin, Shubo; Hu, Yuning; Fu, Hongtuo; Jiang, Sufei; Xiong, Yiwei; Qiao, Hui; Zhang, Wenyi; Gong, Yongsheng; Wu, Yan (Frontiers in Genetics, 2021)
Previous studies have revealed that SDHB has potential functions in the male sexual differentiation and development in M. nipponense through providing ATP. In this study, the functions of Mn-SDHB were further analyzed in depth using quantitative polymerase chain reaction (qPCR), in situ hybridization, western-blot, and RNA interference (RNAi), combined with the histological observations. The full-genome sequence of Mn-SDHB was 54,608 bp at Chromosome 34, including 7 introns and 6 exons. The full-length cDNA sequence of Mn-SDHB was 1,268 base pairs (bp) long with an open reading frame of 807 bp, encoding for 268 amino acids. The highest expression level of Mn-SDHB in different tissues was observed in the testis, and male prawns at post-larval developmental stage 25 during different developmental stages, indicating that SDHB was potentially involved in the male sexual development in M. nipponense. In situ hybridization and western-blot analysis indicated that SDHB plays essential roles in the testis development. The in situ hybridization analysis also implies the potential roles of Mn-SDHB in ovarian development. The expressions of Mn-IAG were decreased after Mn-SDHB dsRNA injection, indicating SDHB has the positive regulatory effects on IAG in M. nipponese. Thus, SDHB was involved in the mechanism of the male sexual development. The testis development was inhibited, and sperms were rarely observed after 10 days of Mn-SDHB dsRNA injection, indicating SDHB has positive effects on the male sexual development in M. nipponense. This study highlights the functions of SDHB in M. nipponense, which provide new insights for the future studies of the male sexual development in other crustacean species.